Implementation Of The Kbsm English Language Curriculum : An Appraisal - Abu Kassim, Noor Lide (Universiti Sains Malaysia, 1989)
The issue concerns the complex process of curr iculum implementation. •In the following chapters. this study discuss this delicate and complex process and the various strategies and approaches which could be adopted for curriculum innovation implementation.